Prevalence of Research Methods in Higher Education in Lampung - Apriyanto, Sigit; Amrizal, Amrizal (CV. Tripe Konsultan, 2025)
Higher education research plays a crucial role in shaping academic quality and advancing knowledge, making it essential to map the methodologies applied in order to assess the direction and relevance of scholarly work. This study focused on mapping the prevalence of research methods employed in higher education studies in Lampung Province, specifically examining the tendencies towards quantitative, qualitative, and mixed-methods approaches, as well as the extent to which new methodologies such as digital ethnography and participatory action research have been adopted. A systematic literature review was conducted on articles, undergraduate theses, master’s dissertations, and doctoral research produced in universities across Lampung between 2015 and 2025, involving identification, classification, and comparative analysis of research methods. The findings reveal the dominance of quantitative approaches, although the past five years have shown a significant increase in qualitative and mixed-methods studies. Meanwhile, innovative methods remain rarely applied but indicate promising potential for future development. The conclusion highlights that methodological choices are not merely technical decisions but also reflections of academic culture and institutional capacity, suggesting that diversifying methodologies is vital to enhance research quality and strengthen its relevance to local contexts.